EUS‐guided gastrojejunostomy: Double‐balloon occlusion theory with experimental study (with video). (19th August 2020) - Itoi, Takao; Tsuchiya, Takayoshi; Matsunami, Yukitoshi; Tonozuka, Ryosuke; Ishii, Kentaro; Tanaka, Reina; Mukai, Shuntaro; Yamamoto, Kenjiro; Nagakawa, Yuichi; Sofuni, Atsushi
Abstract : Highlight This experimental study using a plastic globe and fine‐needle aspiration needle demonstrated that distention of the jejunum is the most important point to avoid mispuncture and misdeployment of devices in endoscopic ultrasonography‐guided gastrojejunostomy. Itoi and colleagues recommend the double‐balloon occlusion method to endosonographers for safe and reliable endoscopic ultrasonography‐guided gastrojejunostomy.